CURRENT APPLICATION OF VITEX AGNUS-CASTUS L., BASED IN USES MENTIONED BY IBN RUSHD – A REVIEW - OLIMAT, SULEIMAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
This is a specific review of Vitex agnus-castus L. (chasteberry) known as Finjinkest and Shajrat Ibrahim (Abraham’s tree) in Arabic, focusing in the current application: V. agnus-castus is listed among other medicinal plants in the ancient book “Al-Kulliyat Fi A-Tibb,” written by the famous Andulasin Philosopher Ibn Rushd. The focus of the study is to review only the uses mentioned in the book, review up to date literature (e.g., Google Scholar, PubMed, and Scopus) and analyzing the current pharmacological properties in link to the active constituents of the plant. The purpose of the present study is to confirm the uses of V. agnus-castus mentioned by Ibn Rushd with modern scientific and pharmacological research. Ethnopharmacological research confirming the uses mentioned by Ibn Rushd, such as treatment internal organs, liver and spleen, erectile dysfunction, and offspring. The results give further insights into the pharmacological activity of V. agnus-castus and confirm the different uses mentioned by Ibn Rushd.